Effect of client-centered counselling therapy in reducing drug addiction among youths in Azare Metropolis - Alhaji , Danladi; Abubakar, U. Haruna; Sani , Abdulra’uf; Musa, B. Sani (Kashere Journal of Education, 2023)
This study was carried out to determine the effectiveness of Client-centered counselling therapy in modifying drug addiction attitudes among youths in Azare Metropolis, Bauchi State. The objective of the study is to determine whether there is difference attitude of those exposed to treatment and those who were not. The research design adopted for this study was quasi-experimental pre-test-post-test control group design. The participants in the study comprised 50 drug addict youths) made up of 40 male and 10 women between the ages of 18-30, who were selected using purposive sampling technique in the study area. The instruments used for data collection are: (1) Drug Addiction Screening Scale (DASS), and Drug Attitude Scale (DAS). Hypotheses formulated tested, the significant difference of the pre and post-test attitudes of the respondents was determined. There were two groups one experimental and the other was control group. The analyses of data were done using independent t-test by pairing pre-test scores. The results show that was significant difference in the post-test scores on the reasons why youths were addicted to drugs? All the items mean score were above the decision mean. There was significant difference in the post-test scores on the effectiveness of client-centered therapy in modifying drug attitude among youths in the study area. There was significant difference in the mean of pre-test and post-test scores on the attitude of youths towards addiction related to client-centered therapy on experimental group only. From the findings reported in this study we conclude that, client-centered therapy is effective in reducing drug addiction attitude among youths in Azare Metropolis. It was recommended that, Government should provide community counselling unit in order to provide services to Youths within the community whose their mentality always is to use drugs in order to feel normal, get away with certain thoughts, or feeling, and to look smart, counsellors should make constant utilization of Client-centered counselling therapy in treatment of substance abuse, in the school and society, and counsellors should make use of therapy when modifying behaviour of youths on substances.